A CONSTRUÇÃO DA IDENTIDADE DO SER PROFISSIONAL SECRETÁRIO NA REGIÃO DO GRANDE ABC - Almeida, Rosana de (2009)
The Great ABC Region is characterized by being the place which pictures in a singular way the conflicts, the changes and the impact of globalization in Brazil and in the world. Different and articulated sectors built a regional planning, which faced the flexibilization, structural unemployment and the reduction of work positions in the great assembly companies of the spare parts industries, among others, and discovered ways of facing the process that spread throughout Brazil and the world. This demanded the professionalization of those people who occupied the position of secretary to attend the needs of multinational companies. From there the executive secretariat position is being consolidated as a profession of intelligent and professional character considered as analytical symbolic. Secretaries broke their old profile by facing the business competition from professional of other areas and it today plays the role of technical adviser dealing with processes and facilitating the taking of decisions. They are professionals of differentiate formation, with technical, behaviouristic and strategic competence. So, this research has as its aim to analyze the process of constructing the identity of the professional secretary of the ABC region, to study the spaces occupied by these professionals through the mapping of the positions they occupy and to construct a time line of these professionals. To achieve this aim we used a documental research, the construction of a time line and he theme history in the region. To achieve these aims we used a time line and the oral theme history, a documental research using the collecting and analysis of data of seven professionals. The inter-disciplinary dialogue between theory and the discourses showed that there is still a cultural stereotype of the profession in the companies but that there is a respect even if veiled showed by superiors and colleagues conquered by the secretary´s persistence and professionalization. The results show that the identity of the secretaries is built by their live experience what gives them a view of individual and professional values that are updated in the many organizations where they work or had worked and within the studied regional context creating variations in their identities.(AU)